Analysis of Vegetation Cover Fulfillment Strategy towards Achieving Land Quality Index in Bontang City - suryadi suryadi; Cathas Teguh; Fajar Apriani (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2026)
This study examines the strategies, challenges, and collaborative efforts involved in fulfilling vegetation cover targets to support the achievement of the Land Quality Index (LQI) in Bontang City, an industrially dynamic region experiencing rapid urban growth. Using a qualitative descriptive research method, the study analyzes policy documents, spatial observations, stakeholder interviews, and secondary data to interpret how vegetation cover is managed and how governance practices influence land quality outcomes. The findings reveal that accelerated urbanization, industrial expansion, and shifting land-use patterns have contributed to fragmented vegetation cover and declining ecological connectivity across the city’s urban and peri-urban zones. Although government policies such as conservation zoning, green open space requirements, and industrial green buffer regulations formally support vegetation protection, their implementation remains inconsistent due to limited enforcement capacity, weak institutional coordination, and varied levels of compliance across stakeholder groups. The analysis also highlights significant disparities in stakeholder engagement, with farmer groups, environmental NGOs, and agricultural agencies showing high levels of involvement, while village governments and local communities demonstrate relatively low participation, indicating the need for improved environmental literacy and technical support. Results emphasize that the effectiveness of vegetation cover fulfillment and LQI improvement depends on cross-sector collaboration, ecological integration in spatial planning, and adaptive governance mechanisms. The study concludes that sustainable land management in Bontang requires not only strong regulatory frameworks but also more inclusive and coordinated stakeholder participation. A holistic, data-driven, and collaborative approach is essential for strengthening ecological resilience and ensuring long-term land quality amid ongoing urban and industrial development.